Pengaruh Suasana Toko, Lokasi, Dan Online Customer Review Terhadap Minat Berkunjung Kembali Konsumen Barbershop Lifestylehub Di Purwokerto - M. Zulfa Royan; Puspita Lianti Putri; Faizal Rizky Yuttama (CV. ITTC INDONESIA, 2025)
The barbershop industry in Indonesia, particularly in Purwokerto, has become increasingly competitive with the emergence of the lifestyle hub concept, which not only provides haircut services but also offers lifestyle experiences such as coffee shops, comfortable waiting areas, and digital access. This condition requires barbershop owners to understand the factors influencing customer loyalty, especially revisit intention. This study aims to analyze the influence of store atmosphere, location, and online customer reviews on revisit intention of consumers at Barbershop Lifestylehub in Purwokerto, employing the Stimulus–Organism–Response (S-O-R) theory, in which these variables act as stimuli affecting consumer responses. A quantitative method with a survey approach was applied, using purposive sampling of 145 respondents who had visited lifestyle hub barbershops. The research instrument was a Likert-scale questionnaire, and the data were analyzed using validity, reliability, normality, multicollinearity tests, and multiple linear regression analysis. The results show that store atmosphere, location, and online customer reviews, both partially and simultaneously, have a positive and significant effect on revisit intention. These findings highlight that a comfortable store atmosphere, strategic location, and positive image on digital platforms are key factors in fostering consumer loyalty.